CORPORATE BRAND MANAGEMENT INMARKETING SYSTEM OF THE REPUBLIC OF UZBEKISTAN - UMAROVA ZULAYKHO TURSUNOVNA; ABDUSALAMOV OLIMJON ESHMIRZAYEVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
The article discusses the concepts of a brand, a brand, features of a corporate brand, their relationship and place in the marketing system, explores the existing scientific concepts of product branding, identifies the components of a corporate brand, discusses the formation and management of these components, develops a model for the formation and management of a corporate brand and an algorithm formation of a corporate brand, a methodology for assessing the position of a corporate brand, including the evaluation of the components of a corporate brand, is proposed, rove Dena testing pattern formation and management of corporate brand for example, one of thelargest industrial holdings.